EXPLORING THE LINK: HOW SERVICE QUALITY INFLUENCES STUDENT SATISFACTION AND FOSTERS LOYALTY IN EDUCATIONAL INSTITUTIONS - Wang, Shangmin; Phawitpiriyakliti, Chaithanaskorn; Terason, Sid (Strategic Perspectives on Business and Marketing Management, 2024)
Student loyalty has improved the sustainable development and survival rate of private universities. The quality of universities' services is an important indicator for measuring the results of private universities. This research aims to explore the mediating role of satisfaction between service quality and student loyalty. The researcher used a random sampling method to collect data from 493 responses of students in private universities in Guangxi. Using SmartPLS 4 software, the relationship between structures was analyzed using partial least squares (PLS) structural equation method. The results indicated that service quality affected student satisfaction, which in turn influenced loyalty. However, service quality had no significant direct impact on loyalty. The impact of service quality on loyalty was indirect, as mediated by satisfaction. Therefore, while improving the quality of university services, university managers should pay more attention to the improvement of student satisfaction, and continuously promote the close connection and recognition of students with colleges and universities, to stimulate and consolidate the loyalty of students.